Corporate Sector Accounting and Auditing in the EU Acquis Communautaire, 3rd Edition - World Bank Group (World Bank, Vienna, 2016)
This report reflects significant changes in European Union (EU) corporate financial reporting since 2011. In June 2013, a new accounting directive was adopted, replacing the fourth and seventh directives on company law. A directive amending the 2006 audit directive and a new audit regulation addressing oversight of the most significant audits were adopted in April 2014. The new legislation, summarized in this guide, is a result of several years of drafting and discussions following the financial crisis of 2008 and it represent a landmark in the EU’s efforts to strengthen its corporate sector accounting and auditing. The accounting directive seeks to enhance the quality of financial reporting and expand it, especially with regard to public interest entities, while reducing the administrative burden for smaller companies. The new audit reporting requirements introduced by the regulation are expected to increase the usefulness of statutory audits of public interest entities, such as listed companies, credit institutions, and insurance undertakings, and reduce risks of excessive familiarity between statutory auditors and their clients, encourage professional skepticism, and limit conflicts of interest. The audit directive and the regulation will bring more consistency in audit oversight and quality assurance systems across Europe. Implementation will involve significant challenges and require increased resources to ensure systems function effectively.